2021
DOI: 10.1186/s12951-021-00813-8
|View full text |Cite
|
Sign up to set email alerts
|

Selective mediation of ovarian cancer SKOV3 cells death by pristine carbon quantum dots/Cu2O composite through targeting matrix metalloproteinases, angiogenic cytokines and cytoskeleton

Abstract: It was shown that some nanomaterials may have anticancer properties, but lack of selectivity is one of challenges, let alone selective suppression of cancer growth by regulating the cellular microenvironment. Herein, we demonstrated for the first time that carbon quantum dots/Cu2O composite (CQDs/Cu2O) selectively inhibited ovarian cancer SKOV3 cells by targeting cellular microenvironment, such as matrix metalloproteinases, angiogenic cytokines and cytoskeleton. The result was showed CQDs/Cu2O possessed antica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…The morphological alterations of non-small lung cancer (A549 cell line) exposed to CB-CQDs, N-CQDs, and FA-NCQDs were studied using Acridine orange/Ethidium bromide (AO/EtBr), DAPI, Crystal violet, and Propidium iodide stains [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The morphological alterations of non-small lung cancer (A549 cell line) exposed to CB-CQDs, N-CQDs, and FA-NCQDs were studied using Acridine orange/Ethidium bromide (AO/EtBr), DAPI, Crystal violet, and Propidium iodide stains [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, MCF-7 cells treated with N-CQDs for 48 h had a minor rise in G1 phase cell numbers (56 ± 1.4%). While there was a significant decrease in S phase cell numbers (12 ± 0.3%), (Figure 13) (D. Chen et al, 2021;Feng et al, 2020).…”
Section: N-cqds Induce Cell Cycle Arrestmentioning
confidence: 96%
“…Cu-metal-organic framework (MOF) materials are capable of destroying the structural integrity of F-actin which is the cytoskeleton component of ovarian cancer cells, thus inducing tumor cell necrosis 118 . Chen et al firstly fabricated TME targeted CQDs/Cu 2 O nanocomplexes for ovarian cancer treatment 47 . A series of in vitro experiments showed that CQDs/Cu 2 O could not only destroy the structural integrity of F-actin but also cause downregulatory expression of MMP-2/9 and VEGFR2, which greatly hindered angiogenesis in TME.…”
Section: Carbon Nanomaterials For Cancer Treatmentmentioning
confidence: 99%